Lenguas en desplazamiento. Representaciones literarias de problemáticas lingüísticas en la e(in)migración italiana en Argentina - Bravo Herrera, Fernanda (Universidad Nacional del Litoral, 2019)
The objective of this paper is to analyze in a significant selection of Italian and Argentinean texts the different representations of linguistic problems linked to the phenomenon of Italian e(in)migration in Argentina. Reading, from comparative and socio-critical literature, aims to reconstruct the various ideological perspectives that make up cultural encounters caused by migratory movements, which determine identity restructuring and are visible in linguistic rearrangements, through conflicts or their resolutions. In this way, it is expected to outline, in the inscription of the linguistic representations and stylizations, a semiotic reading of the identity reconfigurations in connection with the migratory processes.